2022
DOI: 10.1007/s00784-022-04381-5
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous ibuprofen versus diclofenac plus orphenadrine in orthognathic surgery: a prospective, randomized, double-blind, controlled clinical study

Abstract: Objectives The aim of this prospective, randomized, double-blind, controlled clinical study was to evaluate the analgesic effect of ibuprofen versus diclofenac plus orphenadrine on postoperative pain in orthognathic surgery. Material and methods Patients who underwent orthognathic surgery were randomized into two groups to receive intravenously either 600 mg of ibuprofen (I-group) or 75 mg diclofenac plus 30 mg orphenadrine (D-group), both of which were gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…They found no significant difference between the sides of the mouth for pain, swelling, or trismus in the first 48 hours. Tomic et al 38 compared the analgesic effects of intraoperative and postoperative administration of intravenous orphenadrine and diclofenac with ibuprofen alone in patients undergoing orthognathic surgery and found no significant difference in pain intensity.…”
Section: Resultsmentioning
confidence: 99%
“…They found no significant difference between the sides of the mouth for pain, swelling, or trismus in the first 48 hours. Tomic et al 38 compared the analgesic effects of intraoperative and postoperative administration of intravenous orphenadrine and diclofenac with ibuprofen alone in patients undergoing orthognathic surgery and found no significant difference in pain intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Tomic et al . [ 18 ] showed that diclofenac, as an adjacent to orphenadrine, was effective in significantly reducing POP. Similarly, Yuri et al .…”
Section: Introductionmentioning
confidence: 99%
“…(trismus), paresthesia, and so on [5]. To minimize symptoms and accelerate patient recovery, some pharmacological and nonpharmacological protocols have been extensively studied and used, such as cryotherapy, anti-inflammatory and analgesics, kinesiotaping, lymphatic drainage, vitamin complex supplementation, electroacupuncture, photobiomodulation (PBM) therapy, and so on [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, regardless of the technology used, good surgical technical skills, reduced surgical time, and appropriate management of the oral mucosa and facial tissues, some unwanted postoperative symptoms are expected, such as pain, edema, limited mouth opening (trismus), paresthesia, and so on [5]. To minimize symptoms and accelerate patient recovery, some pharmacological and nonpharmacological protocols have been extensively studied and used, such as cryotherapy, anti‐inflammatory and analgesics, kinesiotaping, lymphatic drainage, vitamin complex supplementation, electroacupuncture, photobiomodulation (PBM) therapy, and so on [6–12].…”
Section: Introductionmentioning
confidence: 99%